Leucocyte recruitment and molecular fortification of keratinocytes triggered by streptococcal M1 protein. (19th October 2017) - Persson, Sandra T.; Hauri, Simon; Malmström, Johan; Herwald, Heiko
Abstract: Streptococcus pyogenes of the M1 serotype is commonly associated with invasive streptococcal infections and development of streptococcal toxic shock syndrome. The M1 protein is a powerful inducer of inflammatory responses for several human cell types, but the reason why M1 protein‐related strains is over‐represented in invasive streptococcal diseases is still not understood. This study was undertaken to investigate if soluble M1 protein can aggravate the severity of streptococcal skin infections in respect to inflammation, leucocyte recruitment, and tissue remodelling as seen in patients with cellulitis and necrotizing fasciitis. We found that HaCaT cells are able to recruit activated leucocytes when encountering M1 protein. Neither the bacterial protein nor activated leucocytes caused cell damage on HaCaT cells, instead HaCaT cells responded to the bacterial virulence factor by releasing several proteins protective against bacterial infection and leucocyte responses. However, although not cytotoxic, M1 protein completely abolished wound healing abilities of HaCaT cells. Taken together, our results demonstrate that M1 protein is a critical virulence factor that can augment streptococcal skin infection suggesting that the protein is an interesting target for drug development.